Analisis Sentimen TikTok Shop pada Media Sosial Twitter Menggunakan Algoritma Naïve Bayes - Kariman, Delsi; Mardiyah, Ainil; Junios, Junios; Sari, Lisma; Ananda, Muthia; Jasril, Jasril (STMIK Banjarbaru, 2025)
The progress of TikTok Shop as an e-commerce platform has generated various public responses, including both support and criticism. Therefore, sentiment analysis is needed to determine user opinion. The purpose of this study is to categorize Twitter users' sentiments about TikTok Shop into positive, negative, and neutral categories. Data was collected through web scraping techniques, followed by pre-processing stages, namely case folding, tokenization, stopword removal, and stemming. Next, features were extracted using Term Frequency-Inverse Document Frequency (TF-IDF). The Naïve Bayes algorithm was applied to classify the sentiment in the processed tweets. To perform the evaluation, a confusion matrix was used with accuracy, precision, recall, and F1-score metrics. The evaluation results show that the model achieves high accuracy (0.9602). However, the model experiences problems in classifying minority classes, namely positive and negative classes, due to an unbalanced class distribution, with neutral classes dominating the dataset. These findings highlight the importance of addressing class imbalance to improve model performance in predicting positive and negative sentiment.Keywords: Sentiment Analysis; TikTok Shop; Social Media; Twitter; Naïve Bayes AbstrakKemajuan TikTok Shop sebagai platform e-commerce memunculkan berbagai tanggapan publik yang mencakup dukungan maupun kritik. Oleh karena itu, untuk mengetahui opini pengguna diperlukan analisis sentimen. Tujuan penelitian adalah untuk membagi sentimen pengguna Twitter tentang TikTok Shop menjadi kategori positif, negatif, dan netral. Data dikumpulkan melalui teknik web scraping kemudian diikuti tahap pre-pemrosesan, yaitu case folding, tokenisasi, stopword removal, dan stemming. Selanjutnya fitur diekstraksi menggunakan Term Frequency-Inverse Document Frequency (TF-IDF). Algoritma Naïve Bayes diterapkan untuk mengklasifikasikan sentimen pada tweet yang telah diproses. Untuk melakukan evaluasi, confusion matrix digunakan dengan metrik akurasi, precision, recall, dan F1-score. Hasil evaluasi menunjukkan bahwa model mencapai akurasi yang tinggi (0,9602). Namun, model mengalami masalah dalam klasifikasi kelas minoritas, yaitu kelas positif dan negatif, yang disebabkan oleh distribusi kelas yang tidak seimbang, dengan kelas netral yang mendominasi dataset. Temuan ini menunjukkan pentingnya menangani ketidakseimbangan kelas untuk meningkatkan kinerja model dalam memprediksi sentimen positif dan negatif.